Adopting Modern IT Systems Is Vital in Employing Accountants and Internal Auditors (Educational Perspective): A Case Study in Jordan Cement Company – Lafarge - Weshah, Sulaiman (Jordan Journal of Business Administration, 2021)
This study aimed at identifying the role of adopting accounting information systems as a modern IT tool within the employment process inside both of accounting department and internal audit and control department in the practical field. The study depended on the following dimensions (IT infrastructure, information system transformation and IT skills) as a base for employment in the organization, which form the independent variables, while the employment process for accountants and internal auditors forms the dependent variables.By using the analytical descriptive method, a questionnaire was developed and distributed, consisting of (38) sections connected with the study variables within the study society (Jordan Cement Company - Lafarge) as a case study. The society of the study was all of the employees in accounting, internal audit and control and HR departments with a total of 34 employees.The results showed that there was a role of adopting modern IT systems on the employment process for accounting department and internal audit and control department. The modern information system transformation had made the greatest contribution in accountants’ and internal auditors’ employment process.Considering the study results, several recommendations are made, including improving and developing educational skills for accountants. The study recommends educational accounting departments inside universities to employ faculty members who have the capabilities to teach and use information systems in the practical fields of accounting or auditing. Also, organizations need to support employees’ training to improve their IT skills to match the needs within the computerized information systems transformation.